Cerebellar and Hippocampal Activation During Eyeblink Conditioning Depends on the Experimental Paradigm: A MEG Study. Issue 4 (2003) - Kirsch, Peter; Achenbach, Caroline; Kirsch, Martina; Heinzmann, Matthias; Schienle, Anne; Vaitl, Dieter
Abstract : The cerebellum and the hippocampus are key structures for the acquisition of conditioned eyeblink responses. Whereas the cerebellum seems to be crucial for all types of eyeblink conditioning, the hippocampus appears to be involved only in complex types of learning. We conducted a differential conditioning study to explore the suitability of the design for magnetencephalography (MEG). In addition, we compared cerebellar and hippocampal activation during differential delay and trace conditioning. Comparable conditioning effects were seen in both conditions, but a greater resistance to extinction for trace conditioning. Brain activation differed between paradigms: delay conditioning provoked activation only in the cerebellum and trace conditioning only in the hippocampus. The results reflect differential brain activation patterns during the two types of eyeblink conditioning.